2014 Sixth International Workshop on Quality of Multimedia Experience (QoMEX) 2014
DOI: 10.1109/qomex.2014.6982305
|View full text |Cite
|
Sign up to set email alerts
|

Assessing effect sizes of influence factors towards a QoE model for HTTP adaptive streaming

Abstract: HTTP Adaptive Streaming (HAS) is employed by more and more video streaming services in the Internet. It allows to adapt the downloaded video quality to the current network conditions, and thus, avoids stalling (i.e., playback interruptions) to the greatest possible extend. The adaptation of video streams is done by switching between different quality representation levels, which influences the user perceived quality of the video stream. In this work, the influence of several adaptation parameters, namely, swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
102
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 17 publications
15
102
4
Order By: Relevance
“…The results indicated that the delivered representation bitrate and the number of stalls were the main influence factors on the QoE. Finally, [8,14,33] presented surveys on the studies related to various influence factors of QoE in HTTP adaptive streaming.…”
Section: Related Workmentioning
confidence: 96%
See 1 more Smart Citation
“…The results indicated that the delivered representation bitrate and the number of stalls were the main influence factors on the QoE. Finally, [8,14,33] presented surveys on the studies related to various influence factors of QoE in HTTP adaptive streaming.…”
Section: Related Workmentioning
confidence: 96%
“…Of the related works mentioned above, the subjective experiments in [14,28] were conducted by crowdsourcing. In [14], authors analyse the effect of switch amplitude (i.e., quality level difference), switching frequency, and recency effects on HAS Quality of Experience (QoE) while in [28], authors analyse the effect of average representation bitrate (i.e., media throughput at the client), average startup time (or startup delay), and average number of stalls on existing DASH-based Web clients.…”
Section: Related Workmentioning
confidence: 99%
“…The problem of QoE assessment in HTTP video streaming is already well-known and well studied, and different QoE models for video streaming have been proposed in the past [7], [10], [12], [13], [15], [21], [23]- [25]. Today it is well accepted that stalling (i.e., stops of the video playback) and initial delay on the video playback are the most relevant KPIs for video streaming QoE [12]- [14], [23].…”
Section: Related Workmentioning
confidence: 99%
“…Today it is well accepted that stalling (i.e., stops of the video playback) and initial delay on the video playback are the most relevant KPIs for video streaming QoE [12]- [14], [23]. Quality switches have also a relevant impact on QoE when considering adaptive video streaming technology [15]; however, in [11] we recently found that QoE for video streaming in modern smartphones is actually slightly impaired by resolution switches, mainly due to the screen size of such devices. Recent studies [21] show that the position of stallings and their length have a relevant impact on QoE, but do not attempt to use such metrics to improve QoE predictions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation